2022
DOI: 10.1093/braincomms/fcac263
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal brain state distribution and network connectivity in aSYNGAP1rat model

Abstract: Mutations in the SYNGAP1 gene are one of the common predictors of neurodevelopmental disorders, commonly resulting in individuals developing autism, intellectual disability, epilepsy, and sleep deficits. EEG recordings in neurodevelopmental disorders show potential to identify clinically translatable biomarkers to both diagnose and track the progress of novel therapeutic strategies, as well as providing insight into underlying pathological mechanisms. In a rat model of SYNGAP1 haploinsufficiency in which the e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…61 Mitogen-activated protein kinases phosphorylate core clock gene regulators [62][63][64][65][66][67] , and these pathways are affected in SYNGAP1, NLGN3, FMR1 and SCN2A deficient mice and rats [68][69][70][71] , which also present with sleep impairments. 22,70,72,73 Thus, inadequate GluN2B cellular signalling could in part contribute to the sleep alterations observed in Grin2b +/mutants. Future work will need to investigate whether dysregulation in diurnal behavioural patterns is present, and whether and to what extent mitogen-activated protein kinase activity and clock gene modulation is affected by GluN2B haploinsufficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…61 Mitogen-activated protein kinases phosphorylate core clock gene regulators [62][63][64][65][66][67] , and these pathways are affected in SYNGAP1, NLGN3, FMR1 and SCN2A deficient mice and rats [68][69][70][71] , which also present with sleep impairments. 22,70,72,73 Thus, inadequate GluN2B cellular signalling could in part contribute to the sleep alterations observed in Grin2b +/mutants. Future work will need to investigate whether dysregulation in diurnal behavioural patterns is present, and whether and to what extent mitogen-activated protein kinase activity and clock gene modulation is affected by GluN2B haploinsufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…We utilized a previously published automatic SWD detector algorithm to quantify SWDs. 22,23 Spectral analysis allowed for the identification of harmonic peaks in the SWD frequency range. The code used for analysis is available at https://github.com/Gonzalez-Sulser-Team/SWD-Automatic-Identification.…”
Section: Absence Seizure Detection and Sleep-wake Scoringmentioning
confidence: 99%
“…Power spectral analysis, herein, identified harmonic peaks. Using the earlier described methodology, that defined sleep stages (NREM sleep, REM sleep or wake), using 5 s recording epochs, it was reported that Syngap +/Δ−GAP rats spent an equivalent percentage of time in all states when compared with WT littermate controls 54 , but exhibited less NREM and wake bouts, similar to our report that found reduced amount of time in slow wave sleep and wake, albeit differing from the report herein that identified substantially elevated delta power (<p<0.0001) and significantly elevated theta spectral power (<0.05). Direct comparison of our data presented herein is complicated given the vastly different methodologies, species, EEG acquisition time, channels utilized to acquire data, and analysis of the signal.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, over 20 years since its discovery, we have built on earlier work to identify a combinatorial and corroborative report on electro-and neurophysiological biomarkers for SRID precision therapeutic development 54,75,[77][78][79] . Our key novelty, from prior reports, lies in the reporting and analytic combination of: i) in vitro HD-MEA recording and analysis using dissociated and plated cortical neurons from WT and Syngap1 +/cortices, in parallel, with ii) in vivo wireless, cortical EEG, capturing cortical circuitry and bridging 2D in vitro electrophysiological properties with 3D, live, awake, behaving, in vivo neurophysiological outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation